Islamic Motivation, Job Placement, and Work Environment through Employee Performance at Darussalam Press in Pondok Modern Darussalam Gontor - Lathiefa Rusli; Muhammad Fahmi Hasan; Fajar Surya Ari Anggara (Al Tijarah, 2023)
As a printing center at Pondok Modern Darussalam Gontor (PMDG), Darussalam Press is required to be able to fulfill all the needs for textbooks for PMDG. In order to complete these demands, Darussalam Press is required to improve the performance on its employees. This research aims to find out and analyze the influence of Islamic motivation, job placement and work environment on employee performance at Darussalam Press. The research uses a quantitative descriptive method, with a total sample of 50 respondents through a questionnaire. The analytical method used is Partial Least Square (PLS) with a coefficient test in the form of an outer model and an inner model. The results showed that Islamic motivation had no effect on performance as t-test 1.855 <2.012 t-table and P values 0.064 > 0.05. Job placement has an influence on performance as t-test 3,291 > 2,012 t-tables and P values 0.001<0.05. The work environment has an influence on performance as t-test 4,307 > 2,012 t-tables and P values 0,000 <0.05. For Darussalam Press, it is better to increase the Islamic motivation on employees at Darussalam Press, such as providing understanding to employees so that work is intended as worship, work honestly, work for good in this world and the hereafter and so on so that employee performance can increase.